A MULTIMODEL ENSEMBLE APPROACH TO ASSESSMENT OF CLIMATE CHANGE IMPACTS ON THE HYDROLOGY AND WATER RESOURCES OF THE COLORADO RIVER BASIN - Christensen N.; Lettenmaier D.P. (My University, 2006)
Implications of 21st century climate change on the hydrology and water resources of the Colorado River basin were assessed using a multimodel ensemble approach in which downscaled and bias corrected output from 11 General Circulation Models (GCMs) was used to drive macroscale hydrology and water resources models. Downscaled climate scenarios (ensembles) were used as forcings to the Variable Infiltration Capacity (VIC) macroscale hydrology model, which in turn forced the Colorado River Reservoir Model (CRMM). Ensembles of downscaled precipitation and temperature, and derived streamflows and reservoir system performance were assessed through comparison with current climate simulations for the 1950-1999 historical period. For each of the 11 GCMs, two emissions scenarios (IPCC SRES A2 and B1, corresponding to relatively unconstrained growth in emissions, and elimination of global emissions increases by 2100) were represented. Results for the A2 and B1 climate scenarios were divided into period 1 (2010-2039), period 2 (2040-2069), and period 3 (2070-2099). The mean temperature change averaged over the 11 ensembles for the Colorado basin for the A2 emission scenario ranged from 1.2 to 4.4°C for periods 1-3, and for the B1 scenario from 1.3 to 2.7°C. Precipitation changes were modest, with ensemble mean changes ranging from -1 to -2 percent for the A2 scenario, and from +1 to -1 percent for the B1 scenario. An analysis of seasonal precipitation patterns showed that most GCMs had modest reductions in summer precipitation and increases in winter precipitation. Derived 1 April snow water equivalent declined for all ensemble members and time periods, with maximum (ensemble mean) reductions of 38 percent for the A2 scenario in period 3. Runoff changes were mostly the result of a dominance of increased evapotranspiration over the seasonal precipitation shifts, with ensemble mean runoff reductions of -1, -6, and -11 percent for the A2 ensembles, and 0, -7, and -8 percent for the B1 ensembles. These hydrological changes were reflected in reservoir system performance. Average total basin reservoir storage generally declined, however there was a large range across the ensembles. Releases from Glen Canyon Dam to the Lower Basin (mandated by the Colorado River Compact) were reduced for all periods and both emissions scenarios in the ensemble mean. The fraction of years in which shortages occurred increased by approximately 20% by period 3 in for both emissions scenarios, and the average shortage increased to a maximum of 3.7 BCM/yr for the period 3 A2 ensemble average. Hydropower output was reduced in the ensemble mean for all time periods and both emissions scenarios.